IMPLEMENTASI ASAS KEPASTIAN HUKUM YANG BERKEADILAN BERDASAR CITA HUKUM BANGSA INDONESIA (Kajian Putusan Pengadilan Negeri Banyumas tentang kasus mbah Minah) - Iskandar Wibawa (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
Legality is one basic of penal law beside culpability in deciding the punishment. Legality is often perceived similar to law enforcement. According to Article 1 (1) of the Penal Law (KUHP), the law refers to written law. In fact, there is also living law mentioned in the Constitution. This kind of situation often causes the judge decision fails to meet social justice since the decision is merely based on formal law and neglected material law, such as in the case of Minah in Banyumas Court. Thus, progressive approach is necessitated in order to understand legality both in formal and material law in accordance with national legal ideals, Pancasila.